From fruit growth to ripening in plantain: a careful balance between carbohydrate synthesis and breakdown - Campos, Nadia A.; Colombié, Sophie; Moing, Annick; Cassan, Cedric; Amah, Delphine; Swennen, Rony L.; Gibon, Yves; Carpentier, Sebastien C. (Oxford University Press, 2022)
We investigated the fruit development in two plantain banana cultivars from two weeks after bunch emergence till twelve weeks through high-throughput proteomics, major metabolite quantification and metabolic flux analyses. We aimed to investigate for the first time different fruit development stages and gain unique insights into the order of appearance and dominance of specific enzymes/fluxes. Starch synthesis and breakdown are processes that take place simultaneously. During the first ten weeks fruits accumulated up to 48% of starch. Glucose 6-phosphate and fructose were important starch precursors. We found a unique amyloplast transporter and hypothesize that it facilitates the import of fructose. We identified an invertase originating from the M. balbisiana genome that would enable to flow carbon back to growth and starch synthesis and keep a high starch content even during ripening. Enzymes associated to the initiation of ripening were involved in ethylene and auxin metabolism, starch breakdown, pulp softening and ascorbate biosynthesis. The initiation of ripening was cultivar specific. A faster initiation was particularly linked to 1-aminocyclopropane-1-carboxylate oxidase and 4-alpha glucanotransferase disproportioning enzyme. This knowledge is fundamental to determine the ideal harvest moment, reduce postharvest losses and improve product quality through breeding.